The dawn of hope a memoir of Ravensbrück - Gaulle-Anthonioz, Geneviève de 1920-2002 (Arcade Publ., 1999)
Genevieve de Gaulle (niece of General Charles de Gaulle) became a resistance fighter in the summer of 1940 as the Germans occupied Paris. Three years later she is arrested and sent to the Fresnes Prison where she is transferred to the Nazi death camp, Ravensbruck for the remainder of the war until liberation in 1945.
Keywords: Gaulle-Anthonioz, Geneviève de; Gaulle-Anthonioz, Geneviève de -- 1920-2002; Ravensbrück (Concentration camp); Konzentrationslager Ravensbrück; Geschichte 1944-1945; Weltkrieg (1939-1945); World War, 1939-1945 -- Personal narratives, French; World War, 1939-1945 -- Prisoners and prisons, German; Résistance; Französin; Autobiografie -- 1944-1945; Erlebnisbericht